Towards a more capacious, kindly,and caring criticality: A post-critical manifesto for ethical-relational-creative reviewing - Taylor, Carol A. Taylor; Hewlett, Sally; Hogarth, Hannah (Critical Studies in Teaching and Learning, 2023)
The words ‘criticality’, ‘critical’,and ‘critique’can often summon up painful, exposing,and difficult experiences. In  a  higher  education system shaped  by hierarchical cultures, abuses  of  power, performative metrics andcompetitiveness, many of us are often positioned as (and internalise a sense of ourselves as) lacking. This imputed sense of ‘lack’ begins early in our educational careersand its affective impress often stays with us. As PhD students, we are required to subject ourselves to critique in order topass confirmation processes; as article authors, our work stands or falls at the critical hands  of  journal  reviewers  and  editors  who,  as  gatekeepers,  decide  which  of  us  is ‘accepted’ or ‘rejected’.We write as four members of the larger Get Up and Move!Collective, using the special issue call from CriSTaL to explore criticality, critical, critique, to revisit our own contested entanglements in/with criticality in higher education. We deploy the methodological approaches  of  compositing  and  composting  to ponder  the  inimical  conditions, negative behaviours,and ill-judged peer review comments that give rise to damaging modes of critique. From our work in the Collective, we consider what a more capacious, kindly,and caring criticality might look, feel,and be like. The article ends with APost-Critical Manifesto for Ethical-Relational-Creative Reviewing, which outlines a praxis for doing criticality differently.